Infant oral health: Knowledge, attitude and practices of parents in Udaipur, India - Ramesh Nagarajappa; Gauri Kakatkar; Archana J Sharda; Kailash Asawa; Gayathri Ramesh; Nagarajappa Sandesh (Wolters Kluwer Medknow Publications, 2013)
Background: The aim of this study was to assess the infant oral health (IOH) related knowledge, attitudes and practices (KAP) of parents in Udaipur, India. Materials and Methods: A cross-sectional descriptive study was conducted among 470 parents visiting the Department of Pediatrics, Rabindranath Tagore Medical College and Hospital. A 32-item questionnaire covering socio-demographic characteristics and questions pertaining to KAP regarding IOH care was used to collect the data. Descriptive statistics, Student's t-test, one-way analysis of variance, and Scheffe's test were used for the statistical analysis (P ≤ 0.05). Results: Majority of the parents had good knowledge regarding tooth eruption, but had a poor knowledge of cleaning (58.7%) and development of caries (48.5%). Parents in the age group of 25-30 years showed significantly higher mean knowledge (25.90 ± 3.93), attitude (15.71 ± 2.23), and practice (20.09 ± 2.50) scores. Female parents showed a significantly higher mean knowledge (21.45 ± 4.27) and attitude scores (14.97 ± 2.15) than the male parents. Conclusion: Parent's knowledge on IOH care was inadequate. Health professionals, who are the first to come into contact with expectant and new mothers, need to disseminate appropriate and accurate information about oral health-care for infants.